Geographic Information System-Based Integrated Imagery Sensing System for Military Operations - Sutharak, Sumeth; Daungklang, Phummipat (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2022)
The IP Web Camera is currently used as a tactical mean for image data acquisition in many operational units of the Royal Thai Air Force. Nevertheless, those image data have not been integrated into a system, called Common Operation Picture (COP), which can further contribute to a competent decision made by the commander of the units. Hence, the researching team created the system by integrating the Geographic Information System (GIS) altogether with the Web Real-Time communication (WebRTC) in order to support the tactical operations. The researching team has conducted the experiment on the use of mobile phone cameras with IP Web Camera and the frame rate of 30 FPS. The experiment results have shown some remarkable performance under the following circumstances; 0.1 – 0.5 Mbps internet for the image size of 180p, 0.5 – 1.0 Mbps internet for the image size of 360p and 1.0 – 2.0 Mbps internet for the image size of 720p.